Comparative genomics of 16 Microbacterium spp. that tolerate multiple heavy metals and antibiotics - Deric R. Learman; Zahra Ahmad; Allison Brookshier; Michael W. Henson; Victoria Hewitt; Amanda Lis; Cody Morrison; Autumn Robinson; Emily Todaro; Ethan Wologo; Sydney Wynne; Elizabeth W. Alm; et al. (PeerJ, 2019)
A total of 16 different strains of Microbacterium spp. were isolated from contaminated soil and enriched on the carcinogen, hexavalent chromium [Cr(VI)]. The majority of the isolates (11 of the 16) were able to tolerate concentrations (0.1 mM) of cobalt, cadmium, and nickel, in addition to Cr(VI) (0.5–20 mM). Interestingly, these bacteria were also able to tolerate three different antibiotics (ranges: ampicillin 0–16 μg ml−1, chloramphenicol 0–24 μg ml−1, and vancomycin 0–24 μg ml−1). To gain genetic insight into these tolerance pathways, the genomes of these isolates were assembled and annotated. The genomes of these isolates not only have some shared genes (core genome) but also have a large amount of variability. The genomes also contained an annotated Cr(VI) reductase (chrR) that could be related to Cr(VI) reduction. Further, various heavy metal tolerance (e.g., Co/Zn/Cd efflux system) and antibiotic resistance genes were identified, which provide insight into the isolates’ ability to tolerate metals and antibiotics. Overall, these isolates showed a wide range of tolerances to heavy metals and antibiotics and genetic diversity, which was likely required of this population to thrive in a contaminated environment.